Voluntary control of corticomuscular coherence through neurofeedback: A proof-of-principle study in healthy subjects. (2nd April 2015) - von Carlowitz-Ghori, K.; Bayraktaroglu, Z.; Waterstraat, G.; Curio, G.; Nikulin, V.V.
Highlights: Proof-of-principle study of corticomuscular coherence (CMC)-based neurofeedback. Subjects were prompted to voluntarily modulate instantaneous CMC strength. Results showed CMC modulation independent of motor output parameters. Abstract: Corticomuscular coherence (CMC) relates to synchronization between activity in the motor cortex and the muscle activity. The strength of CMC can be affected by motor behavior. In a proof-of-principle study, we examined whether independent of motor output parameters, healthy subjects are able to voluntarily modulate CMC in a neurofeedback paradigm. Subjects received visual online feedback of their instantaneous CMC strength, which was calculated between an optimized spatial projection of multichannel electroencephalography (EEG) and electromyography (EMG) in an individually defined target frequency range. The neurofeedback training consisted of either increasing or decreasing CMC strength using a self-chosen mental strategy while performing a simple motor task. Evaluation of instantaneous coherence showed that CMC strength was significantly larger when subjects had to increase than when to decrease CMC; this difference between the two task conditions did not depend on motor performance. The exclusion of confounding factors such as motor performance, attention and task complexity in study design provides evidence that subjects were able to voluntarily modify CMC independent of motor output parameters. Additional analysis further strengthened the assumption that the subjects' response was specifically shaped by the neurofeedback. In perspective, we suggest that CMC-based neurofeedback could provide a therapeutic approach in clinical conditions, such as motor stroke, where CMC is altered.